Effect of sonotherapy on symptoms of carpal tunnel syndrome - Ciechanowska, Katarzyna; Łukowicz, Małgorzata (Journal of Education, Health and Sport, 2017)
Admission. Carpal tunnel syndrome (CTS) is one of the most common peripheral neuropathies of the upper limb, which is caused by an increase in pressure in the wrist canal or a decrease in its volume leading to compression and mediated nerve endothelial dysfunction. This disease significantly affects the quality of life of patients, limiting its manual capabilities and ability to perform daily activities. Therefore, finding effective treatments for this condition is linked to social needs. The main purpose of the study was to evaluate the influence of ultrasonic wave therapy on the symptoms of carpal tunnel syndrome. Material and methods. Twenty patients with neuropathy diagnosed with carpal tunnel syndrome were included in the study. Patients underwent sonotherapy. Before and after treatment pain scores measured with VAS and modified Laitinen questionnaire, pain grip strength and surface sensation in the midrange area were assessed. Probable tests have also been used most often in patients with CTS Results and conclusions. Ultrasonic wave therapy increases the painless grip strength, reduces visual ailments - analog VAS scale and modified Laitinena questionnaire, and significantly improves surface sensation in the mediated nerve domain of patients with CTS.